Presenting your research / Saidatul Akmar Zainal Abidin, Asiah Jamil and Nurzeti Ghafar - Zainal Abidin, Saidatul Akmar; Jamil, Asiah; Ghafar, Nurzeti (UiTM Press, 2023)
This is a book which offers ideas for many of us who are expected to conduct an oral presentation for various reasons such as a school project, college research or assignments, and a project or report at work. This could include research proposal, academic research/project, a postgraduate thesis, and other research reports which are academic as well as non-academic in nature such as those presented at the workplace. The book also outlines: the format/structure, content, and especially the delivery aspects of an oral presentation such as the use of language, non-verbal skills, the use of visual aids and the importance of feedback. In addition, it proposes a set of criteria used for the assessment of an oral presentation.